John Steinbeck and Angel - Denton Cox (Steinbeck's doctor):::Creator::::::::::::
John Steinbeck sitting and petting Angel Biddle Duke, his bull terrier, while in a daybed in his sitting room. Angel was often called 'the white pig' by Steinbeck's friends. See also number 0-288. Color. Original in safe